DAMPAK PENGGUNAAN TWITTER TERHADAP PEMBELAJARAN BAHASA INGGRIS (DITINJAU DARI PERSEPSI MAHASISWA) - BANDJAR, DEDDY APRIANTO; WAROUW, MAYA P.; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
DAMPAK PENGGUNAAN TWITTER TERHADAP PEMBELAJARAN BAHASA INGGRIS(DITINJAU DARI PERSEPSI MAHASISWA)Deddy A. Bandjar1Maya P.Warouw2Andriyani Marentek3 ABSTRACTThis research is entitled ?Dampak Penggunaan Twitter Terhadap Pembelajaran Bahasa Inggris (Ditinjau dari Persepsi Mahasiswa)?.The objectives of this research are to identify and analyze the effects and learning strategy by using Twitter on learning English based on Cohen (2011) and Chamot (2011) theories. The learning strategies focused on the function are metacognition, cognition, affection, social and then the ones focused on the application are listening, speaking, writing, and reading skills.The writer used qualitative methods in order to analyze and collect students? perceptions about the effects and learning strategies of using Twitter on learning English. The location of the data collection itself was at the English Departement of The Faculty of Humanities, Sam Ratulangi University. The writer selected 10 students who used Twitter as the data of this research. The tools of this research was using open-ended interview by Cresswell (2012) theory.The result of this research showed that there were some negative and positive effects of using Twitter on learning English based on students perception. Besides, there were also learning strategies that students used for improving their ability on learning English skills, which were metacognition, cognition, affection and social. This research used by Cohen (2011) and Chamot?s (2011) theories about the learning strategies of using Twitter on learning English.                                                                                                                                              Keyword: English learning, Students? perception, Twitter use and effect